Effects of Adding Silica Fume and Empty Fruit Bunch to the Mix of Cement Brick - Jen Hua Ling; Yong Tat Lim; Wen Kam Leong; How Teck Sia (Faculty of Engineering and Technology, Sampoerna University, 2021)
Silica fume (SF) and palm oil empty fruit bunch (EFB) are the by-products of the ferroalloy smelting industry and oil palm plantation, which require proper disposal to minimize the environmental impacts. To consume the by-products, the feasibility of utilizing SF and EFB to fabricate bricks was studied. Limited studies were adopting EFB as the natural fibres in bricks and its pro-portion barely exceeded 5%. With the enhancement of SF, EFB content in the mix could be increased. In this study, 336 specimens were produced in the cement-to-sand (c/s) ratios of 1:2.5 and 1:3, where SF replaced 10% to 15% cement in the mix by weight while EFB substituted 20% to 25% sand by volume. The specimens were tested for the compressive strength, density, and water absorption properties. SF was found to strengthen the mix, while EFB reduced the compressive strength and increased the water absorption capacity of the brick. Based on the evaluation results, the mix containing less than 10% SF and 20% EFB content was applicable for non-load-bearing brick.